A computational fluid dynamics investigation of endothelial cell damage from glaucoma drainage devices - Basson, Nicol (2024)
Glaucoma drainage devices (GDDs) are prosthetic-treatment devices for treating primary open-angle glaucoma. Despite their effectiveness in reducing intraocular pressures (IOP), endothelial cell damage (ECD) is a commonly known side-effect. There have been different hypotheses regarding the reasons for ECD with one being an induced increase in shear on the corneal wall. A computational fluid dynamics (CFD) model was used to investigate this hypothesis in silico. The Ahmed Glaucoma Valve (AGV) was selected as the subject of this study using an idealised 3D model of the anterior chamber with insertion angles and positions that are commonly used in clinical practice. It was found that a tube-cornea distance of 1.27 mm or greater does not result in a wall shear stress (WSS) above the limit where ECD could occur. Similarly, a tube-cornea angle of 45° or more was shown to be preferable. It was also found that the ECD region has an irregular shape, and the aqueous humour flow fluctuates at certain insertion angles and positions. This study shows that pathological amounts of WSS may occur as a result of certain GDD placements. Hence, it is imperative to consider the associated fluid force interactions when performing the GDD insertion procedure.